What Remains of the House That Albright Built? - Dever, William G. (The Biblical archaeologist, 1993)
What of Albright's methodology, his results as an archaeologist, and his major biblical-historical conclusions remains valid today? Is Albright's chronological framework secure? Are the critical results of his fieldwork at Tell Beit Mirsim trustworthy? Albright's insistence on archaeologically reconstructing the context of Biblical literature may be his most durable, and vital, contribution.